Universidades corporativas: transformando as estruturas de treinamento e desenvolvimento das organizações no Brasil - Pereira, Cláudio de Souza (2001)
This work analyses the application of the so-called corporative university model in business enterprises in Brazil. What are the impacts observed in the training and development structures in companies that adopt learning systems defined within the corporative university? It aims to offer an analytical basis to those interested in the educational tendency of knowledge management as a strategy for a sustained competitive edge in business nowadays.